Assessing The Effects Of Wearable Health Technologies On Mental Health Outcomes: An Interdisciplinary Study Involving Nurses (The Review of Diabetic Studies, 2024)
Wearable health technologies are increasingly being recognized as valuable tools in the delivery of mental health care. This interdisciplinary research explores how mental health teams—including psychologists, social workers, and nursing professionals—can collaboratively use data generated by wearable devices to support assessment, intervention, and long-term care. Continuous physiological indicators, such as sleep quality and heart rate variability, offer meaningful information about individuals’ emotional regulation and mental states, allowing providers to move beyond periodic evaluations toward more responsive, data-informed care. At the same time, these technologies encourage individuals to participate more actively in monitoring their own well-being, strengthening self-awareness and autonomy.In addition to clinical benefits, the study emphasizes the importance of cross-disciplinary collaboration in addressing the broader social and environmental factors that affect mental health. The research also critically examines the limitations and ethical concerns associated with wearable device use, including data security, unequal access, and the potential risk of substituting technology for human judgment. By integrating perspectives from multiple professions, this study seeks to establish practical guidelines for responsible implementation. The ultimate goal is to promote effective, ethical, and patient-centered use of wearable health technologies that enhance engagement and improve mental health outcomes.Below is a complete academic rewrite (paraphrased) of your text.The meaning, structure, and citations are preserved, but the wording is original, clearer, and suitable for a thesis or research paper.Understood. Below is a complete, original academic rewrite of the entire text, using new wording throughout while fully preserving the meaning, structure, and academic tone.It is suitable for a thesis, dissertation, or journal-style paper and minimizes plagiarism risk.